Effects of nebivolol on biomarkers in elderly patients with heart failure - Taneja, Anil K; Gaze, David; Coats, Andrew J S; Dumitrascu, Dan; Spinarova, Lenka; Collinson, Paul; Roughton, Michael; Flather, Marcus D; SENIORS Investigators (International journal of cardiology, 2014)
BACKGROUND: Heart failure activates neurohormones, and elevated levels of brain natriuretic peptide (BNP) are associated with adverse outcomes. The SENIORS trial showed that nebivolol, a highly selective beta-1 antagonist with vasodilating properties, reduced the composite outcome of all cause mortality or cardiovascular hospital admissions in older patients with heart failure. We explored the effects of nebivolol on a range of neurohormones, cytokines and markers of nitric oxide activity in heart failure. METHODS: In a subset of patients in SENIORS we measured N-terminal pro-brain natriuretic peptide (NT-BNP), pro atrial natriuretic peptide (Pro-ANP), endothelin-1 (ET-1), peripheral norepinephrine (PNE), soluble Fas (sFas), soluble Fas-ligand (sFas-L), tumour necrosis factor-alpha (TNF-α), serum uric acid (SUA), symmetrical dimethyl arginine (SDMA), arginine, citrulline and asymmetrical dimethyl arginine (ADMA) at baseline (before study drug), at 6 months and 12 months in a prespecified substudy. RESULTS: One hundred and six patients were enrolled and 75 had a baseline and at least one follow-up sample. There were no significant differences in neurohormone cytokines or nitric oxide markers measured between the two groups at six or twelve months. NT-ProBNP showed a numerical increase in the nebivolol group compared to placebo (P=0.08) and sFas showed a numerical increase in patients on placebo (P=0.08). Mean baseline LVEF was 35% in both groups and at 12 months was 43% on nebivolol group and 34% on placebo group (P=0.01). CONCLUSION: There were trends but no clear changes associated with nebivolol in neurohormones, cytokines or markers of nitric oxide activity in this study of elderly patients with heart failure. Further studies are needed to understand the mechanistic effects of beta blockers on biomarkers in heart failure.
Keywords: výsledek terapie; Adrenergic beta-1 Receptor Antagonists; antagonisté beta-1-adrenergních receptorů; Male; Neurohormones; biologické markery; ethanolaminy; srdeční selhání; Biomarkers; Internationality; Ethanolamines; cytokiny; SENIORS substudy; benzopyrany; neurotransmiterové látky; internacionalita; Aged; mužské pohlaví; senioři; Nebivolol; NT-Pro BNP and beta blockers; dvojitá slepá metoda; Treatment Outcome; Neurotransmitter Agents; senioři nad 80 let; lidé; Benzopyrans; ženské pohlaví; Heart Failure; Humans; Aged, 80 and over; Cytokines; nebivolol; Double-Blind Method; Female; Beta blockers in heart failure